Morfometrik Tubuh Serta Persentase Karkas dan Non Karkas Kerbau Rawa dan Sapi PO Hasil Penggemukkan Secara Feedlot - Siamtiningrum, G.; Putra, B. W.; Priyanto, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Buffalo  has  anatomical  similarity with  cattle, such as  rument  and  body frame. The objective of this study were to body measurement and percentage of carcass and non carcass of swamp buffaloes and PO cattles in the feedlot system. Six heads male of Swamp Buffalo (218 kg) and eight heads male of PO Cattle (217 kg) were maintained in the feedlot system for 10 weeks. The body size was measured during the maintenance and percentage of carcass and non carcass were taken from the calculations of carcass/non carcass weight per live weight ×100%, data was analyzed using t-test method. The results showed that various parts of the body measurement was significant (P<0.05), percentage of carcass was too significant (P<0.01), and percentage of non carcass was not significant (P>0.05).